JENIS-JENIS TUMBUHAN PAKU YANG TERDAPAT DI KELURAHAN BARINGIN KECAMATAN LUBUK KILANGAN KOTA PADANG - Surianti, Marlinda; Nursyahra, Nursyahra; Rizki, Rizki (Pendidikan Biologi, 2013)
ABSTRACTÂ The research background is that there are plant ecosystem changes caused human activity, and we can found that cutting tree in the forest and was changed to farming area and impact to vegetasi of plant around. This research to knowing variant of fern at Kelurahan Baringin Kecamatan Lubuk Kilangan Kota Padang have been done at July â August 2013. Survey and descriptive method used in plant inventory, identification was doing at Botani Laboratory biology STKIP PGRI Sumbar. Result of research obtained 17 species and 9 familia is consist of teresterial fern and epifit fern. Terrestrial fern has many variant such as Blechnum orientale Linn., Nephrolepis biserrata (Sw.) Schott., Nephrolepis hirsutula (Forst. Pr.), Gleichenia linnearis (Burm.) Clarke., Lycopodiella camparum L., Lygodium circinatum Sw., Lygodium volubile Sw., Phymatodes longissima (BI.) J.Sm, Selaginella plana Hieron., Thelypteris abrupt (Desv.) Proctor., Thelypteris khuntii (Desv.) Morton., Thelypteris resinifera (Jerman) Proctor., Thelypteris sp, Macrothelypteris torresiana (Gaudich.) Ching.. and epifit fern consist of Asplenium nidus L., Davalia denticulate (Burm.) dan Drynaria sparsisora Moore.Â